2021
DOI: 10.3390/su13147571
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Desalination via Waste Heat Recovery from Generator of Wind Turbines: How Economical Is It to Use a Hybrid HDH-RO Unit?

Abstract: Over recent years, the concept of waste heat recovery from the generators of wind turbines for driving a thermal-driven desalination system was introduced, and its advantages were highlighted. However, any selection of a bottoming thermal-driven desalination system among different existing technologies should be taken under consideration before making an ultimate recommendation. Unfortunately, no comprehensive comparison is available in the literature to compare the performance as well as the cost aspects of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The hybridization of HDH with RO units is still under study, especially those systems operated via renewable energy sources. Rostamzadeh et al [15] studied an HDH-RO system depending on generated power from a wind turbine besides recovering the waste heat from the generators as a thermal heat source. The system was investigated for two different locations.…”
Section: Proceedings Of the 8 Th International Exchange And Innovatio...mentioning
confidence: 99%
“…The hybridization of HDH with RO units is still under study, especially those systems operated via renewable energy sources. Rostamzadeh et al [15] studied an HDH-RO system depending on generated power from a wind turbine besides recovering the waste heat from the generators as a thermal heat source. The system was investigated for two different locations.…”
Section: Proceedings Of the 8 Th International Exchange And Innovatio...mentioning
confidence: 99%
“…In addition, they compared the MED and RO systems from the point of view thermoeconomic, the comparison revealed that the use of MED can decrease the cost of distillation by 16%. In order to compare the distillation methods in the ISRR systems, Rostamzadeh et al [8] conducted a cost comparison in two different ISRR systems. They juxtaposed the hybrid HDH-RO system and the solo-RO system, both of them driven by dissipating heat of the wind turbine.…”
Section: Introductionmentioning
confidence: 99%